Ventral Striatal Activation During Reward Anticipation Correlates with Impulsivity in Alcoholics - Beck, Anne; Schlagenhauf, Florian; Wüstenberg, Torsten; Hein, Jakob; Kienast, Thorsten; Kahnt, Thorsten; Schmack, Katharina; Hägele, Claudia; Knutson, Brian; Heinz, Andreas; Wrase, Jana (Biological psychiatry (1969), 2009)
Alcohol dependence is often associated with impulsivity, which may be correlated with dysfunction of the brain reward system. We explored whether functional brain activation during anticipation of incentive stimuli is associated with impulsiveness in detoxified alcoholics and healthy control subjects. Nineteen detoxified male alcoholics and 19 age-matched healthy men participated in a functional magnetic resonance imaging (fMRI) study using a monetary incentive delay (MID) task, in which visual cues predicted that a rapid response to a subsequent target stimulus would either result in monetary gain, avoidance of monetary loss, or no consequence. Impulsivity was assessed with the Barratt Impulsiveness Scale-Version 10 (BIS-10). Detoxified alcoholics showed reduced activation of the ventral striatum during anticipation of monetary gain relative to healthy control subjects. Low activation of the ventral striatum and anterior cingulate during gain anticipation was correlated with high impulsivity only in alcoholics, not in control subjects. This study suggests that reduced ventral striatal recruitment during anticipation of conventional rewards in alcoholics may be related to their increased impulsivity and indicate possibilities for enhanced treatment approaches in alcohol dependence.